1971
DOI: 10.1149/1.2408028
|View full text |Cite
|
Sign up to set email alerts
|

Etch Rate Characterization of Borosilicate Glasses as Diffusion Sources

Abstract: For diffusion of boron into silicon from a doped oxide diffusion source, the surface concentration of boron in silicon and B2O3 in the glass at the glass‐silicon interface are independent of diffusion time. In the temperature range studied, the surface concentrations are also independent of temperature and depend only on the dopant concentration in the deposited glass. This dependence is observed as long as the glass thickness is large enough so that the impurity source approximates a semi‐infinite source. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…To obtain the apparent activation energy of crystallization, the k values listed in Table II are 33,34 and 320 -550 kJ/mol, 24 respectively. Only the activation energies of alkaline and alkali ions are close to those needed for the formation of cristobalite and pseudowollastonite, indicating a diffusion-controlling mechanism.…”
Section: June 2001 Devitrification Kinetics and Mechanism Of K 2 O-camentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the apparent activation energy of crystallization, the k values listed in Table II are 33,34 and 320 -550 kJ/mol, 24 respectively. Only the activation energies of alkaline and alkali ions are close to those needed for the formation of cristobalite and pseudowollastonite, indicating a diffusion-controlling mechanism.…”
Section: June 2001 Devitrification Kinetics and Mechanism Of K 2 O-camentioning
confidence: 99%
“…Another possibility is that the phase transformation is controlled by diffusion of alkaline and alkali ions in glass. Extensive literature search results showed that the activation energies needed for the diffusivity of Ca, Sr, Ba, K, B, and Si in silicate glasses are in the range of 175-295, [22][23][24][25] 165-255, 26 -28 175, 29 165-215, 30 -32 345, 33,34 and 320 -550 kJ/mol, 24 respectively. Only the activation energies of alkaline and alkali ions are close to those needed for the formation of cristobalite and pseudowollastonite, indicating a diffusion-controlling mechanism.…”
Section: (2) Devitrification Kinetics and Mechanismmentioning
confidence: 99%
“…The depth in the silicon below this original surface is denoted by y. We in silicon, k «: Dl so that No~N; We expect NJC i to be approximately 0.05 [6]. Graphs of F and G are given by Crank [4].…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion 1 length 2 (Dt)2 associated with the process is, using t = 1 1 0 1/6 hand D? = 0.01~m-h-2 [6], simply 80 A. Since this is somewhat smaller than the total oxide thickness observed, the formation of a barrier layer of that order of magnitude during oxidation is quite plausible.…”
mentioning
confidence: 86%
See 1 more Smart Citation